Search for the radiative decays D + → γρ + and D + → γK *+ - The BESIII collaboration; M. Ablikim; M. N. Achasov; P. Adlarson; O. Afedulidis; X. C. Ai; R. Aliberti; A. Amoroso; Q. An; Y. Bai; O. Bakina; I. Balossino; et al. (Journal of High Energy Physics)
Abstract We search for the radiative decays D + → γρ + and D + → γK *+ using 20.3 fb −1 of e + e − annihilation data collected at the center-of-mass energy s $$ \sqrt{s} $$ = 3.773 GeV by the BESIII detector operating at the BEPCII collider. No significant signals are observed, and the upper limits on the branching fractions of D + → γρ + and D + → γK *+ at 90% confidence level are set to be 1.3 × 10 −5 and 1.8 × 10 −5, respectively.